2005
DOI: 10.1186/1471-2377-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Enucleation and development of cluster headache: a retrospective study

Abstract: Background: Cluster headache (CH) is a neurovascular, primary headache disorder. There are, however, several case reports about patients whose CH started shortly after a structural brain disease or trauma. Motivated by a patient who developed CH 3 weeks after the removal of an eye and by similar case reports, we tested the hypothesis that the removal of an eye is a risk factor for CH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Some patients experience hallucinations associated with loss of vision, and for a small portion of patients, their hallucinations can be debilitating 9-11 . In some patients the missing eye also gives rise to phantom pain and headaches 12, 13 . Personal accounts of the difficulties of losing an eye and associated coping strategies are useful in understanding these phenomena 4, 15-16 .…”
mentioning
confidence: 99%
“…Some patients experience hallucinations associated with loss of vision, and for a small portion of patients, their hallucinations can be debilitating 9-11 . In some patients the missing eye also gives rise to phantom pain and headaches 12, 13 . Personal accounts of the difficulties of losing an eye and associated coping strategies are useful in understanding these phenomena 4, 15-16 .…”
mentioning
confidence: 99%
“…On the other hand, we can reasonably assume that the role played by head trauma may be predominant over that of eye enucleation. If one compares the causes that led to eye enucleation in 112 patients, none of whom developed CH, who were observed by Sörös et al [34] versus the seven patients with CH reported by other authors [20,[22][23][24]30], it can be seen that head trauma was involved in only 35.7% of the former cases and in as much as 71.4% of the latter. Therefore, we think that two different aspects should be considered and discussed separately.…”
Section: Literature Reviewmentioning
confidence: 68%
“…Phantom pain is a form of neuropathic pain [ 20 ], which may be caused by a lesion or disease of the somatosensory system [ 21 ], or may be related to damage of central or peripheral neurons [ 22 ]. It is defined as a feeling of pain in the limb that is no longer present [ 8 , 12 , 13 , 23 , 24 ], being considered an aftereffect of amputation [ 24 ] and affecting a large proportion of amputees, with an incidence of 50–85% [ 20 , 22 , 25 28 ].…”
Section: Review and Discussionmentioning
confidence: 99%
“…Phantom eye syndrome is classified as painless and painful sensations referred to the amputated eye and clearly distinguishable from both cicatrix pain and any other sensory disturbances in or around the cicatrix [ 11 ], and it is always associated with phantom vision, phantom pain, and phantom sensations [ 8 , 10 , 12 , 13 ]. After limb amputation, more than 90% of patients experience phantom phenomena [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%